Thermally irreversible photochromic dithienylethenes - M. M. Krayushkin; B. M. Uzhinov; A. Yu. Martynkin; D. L. Dzhavadov; M. A. Kalik; V. L. Ivanov; F. M. Stoyanovich; L. D. Uzhinova; O. Yu. Zolotarskaya (International Journal of Photoenergy)
A lot of previously unknown derivatives of dithienylperfluorocyclopentene (DTPFCP) were synthesized. It was shown that 2,2′-dialkylsubstituted DTPFCP'S are phtochromes. The quantum yields of forward and backward photochemical reactions and spectral parameters of open and cyclic forms of the photochromes synthesized were measured. An attempt to obtain fluorescing phtochromes by means of introduction of benzoxazolyl, benzthiazolyl and 1,2,4-oxadiazolyl moieties in 5 and 5′ positions of DTPFCP failed; these compounds were synthesized but they do not fluoresce.